2022
DOI: 10.3390/s22134929
|View full text |Cite
|
Sign up to set email alerts
|

Advanced and Complex Energy Systems Monitoring and Control: A Review on Available Technologies and Their Application Criteria

Abstract: Complex energy monitoring and control systems have been widely studied as the related topics include different approaches, advanced sensors, and technologies applied to a strongly varying amount of application fields. This paper is a systematic review of what has been done regarding energy metering system issues about (i) sensors, (ii) the choice of their technology and their characterization depending on the application fields, (iii) advanced measurement approaches and methodologies, and (iv) the setup of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 107 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…The adopted Convolutional Neural Network (CNN) model is developed by Keras (Ten-sorFlow) Deep Learning Python libraries integrated into Konstanz Information Miner (KN-IME) workflow. KNIME is a versatile tool useful for testing supervised algorithms [75][76][77][78][79] and also predicting energy in renewable energetic sources [80,81]. The optimized CNN network is characterized by the following hyperparameters: an input layer with 193 inputs (the input matrix dataset is transposed to obtain as rows the temporal succession and as attributes the name of the nations), a dense layer (193 neurons adopting a ReLU activation function), an output dense layer (193 outputs predicting the next two years using Softmax as activation function), 80% of the dataset as training dataset (from year 2022 to year 2018), 20% of the remaining dataset as a testing dataset (data from last two years, 2019 and 2020), 100 epochs, training batch size equals to 100, Adam optimizer (0.001 as learning rate, beta1 equals to 0.9, beta2 equals to 0.999, epsilon equals to 1E−8.0 as learning rate decay).…”
Section: Deep Learning and Convolutional Neural Network-cnn For The E...mentioning
confidence: 99%
“…The adopted Convolutional Neural Network (CNN) model is developed by Keras (Ten-sorFlow) Deep Learning Python libraries integrated into Konstanz Information Miner (KN-IME) workflow. KNIME is a versatile tool useful for testing supervised algorithms [75][76][77][78][79] and also predicting energy in renewable energetic sources [80,81]. The optimized CNN network is characterized by the following hyperparameters: an input layer with 193 inputs (the input matrix dataset is transposed to obtain as rows the temporal succession and as attributes the name of the nations), a dense layer (193 neurons adopting a ReLU activation function), an output dense layer (193 outputs predicting the next two years using Softmax as activation function), 80% of the dataset as training dataset (from year 2022 to year 2018), 20% of the remaining dataset as a testing dataset (data from last two years, 2019 and 2020), 100 epochs, training batch size equals to 100, Adam optimizer (0.001 as learning rate, beta1 equals to 0.9, beta2 equals to 0.999, epsilon equals to 1E−8.0 as learning rate decay).…”
Section: Deep Learning and Convolutional Neural Network-cnn For The E...mentioning
confidence: 99%
“…The insolation and cell temperature of solar panels primarily define the total generated power by a solar plant. In the research reviews, a whole array of differing MPPT algorithms has been revealed [ 1 , 2 , 4 ]. Among them, the perturbation and observation (P and O) and incremental conductance (INC) algorithms are the most popular due to their easy and simple implementation.…”
Section: Machine Learning Applications For a Solar Plant Systemmentioning
confidence: 99%
“…There are a lot of GO algorithms to create a GMPPT model [ 1 , 2 , 4 ], but all these models have the following disadvantages: power oscillations in the calm mode; the initialization is a critical issue that decrease power; very slow convergence to a GMPP under insolation’s variation, etc. Due to all the above-mentioned disadvantages, GO-based, real-time GMPPT of a solar plant are ineffective while ML technologies provide the required performance.…”
Section: Machine Learning Applications For a Solar Plant Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy balancing, KPI for energy, produced current/voltage (renewable energy systems), correct setting of energy tools (energy of inverters, power of electrical transformers, correct orientation and efficiency of photovoltaic panels, wind turbine vibrations [21], etc.) [22].…”
Section: Energy Productionmentioning
confidence: 99%